Adaptation to visual feedback delays on touchscreens with hand vision - Elie Cattan; Pascal Perrier; François Bérard; Silvain Gerber; Amélie Rochet-Capellan (Experimental Brain Research, 2018)

Do genetic drift and accumulation of deleterious mutations preclude adaptation? Empirical investigation using RAD seq in a northern lacustrine fish - Charles Perrier; Anne‐Laure Ferchaud; Pascal Sirois; Isabel Thibault; Louis Bernatchez (Molecular Ecology, 2017)
Understanding genomic signatures of divergent selection underlying long‐term adaptation in populations located in heterogeneous environments is a key goal in evolutionary biology. In this study, we investigated neutral, adaptive and deleterious genetic variation using 7,192 SNP s in 31 Lake Trout ( Salvelinus namaycush ) populations ( n = 673) from Québec, Canada. Average genetic diversity was low, weakly shared among lakes, and positively correlated with lake size, indicating a major role for genetic drift subsequent to lake isolation. Putatively deleterious mutations were on average at lower frequencies than the other SNP s, and their abundance relative to the entire polymorphism in each population was positively correlated with inbreeding, suggesting that the effectiveness of purifying selection was negatively correlated with inbreeding, as predicted from theory. Despite evidence for pronounced genetic drift and inbreeding, several outlier loci were associated with temperature and found in or close to genes with biologically relevant functions notably related to heat stress and immune responses. Outcomes of gene–temperature associations were influenced by the inclusion of the most inbred populations, in which allele frequencies deviated the most from model predictions. This result illustrates challenge in identifying gene–environment associations in cases of high genetic drift and restricted gene flow and suggests limited adaptation in populations experiencing higher inbreeding. We discuss the relevance of these findings for the conservation and management, notably regarding stocking and genetic rescue, of Lake Trout populations and other species inhabiting highly fragmented habitats.

Maximal tachycardia and high cardiac strain during night shifts of emergency physicians - Frédéric Dutheil; Fouad Marhar; Gil Boudet; Christophe Perrier; Geraldine Naughton; Alain Chamoux; Pascal Huguet; Martial Mermillod; Foued Saâdaoui; Farès Moustafa; Jeannot Schmidt (International Archives of Occupational and Environmental Health, 2017)

Investigating the extent of parallelism in morphological and genomic divergence among lake trout ecotypes in Lake Superior - Alysse Perreault‐Payette; Andrew M. Muir; Frederick Goetz; Charles Perrier; Eric Normandeau; Pascal Sirois; Louis Bernatchez (Molecular Ecology, 2017)
Understanding the emergence of species through the process of ecological speciation is a central question in evolutionary biology which also has implications for conservation and management. Lake trout ( Salvelinus namaycush ) is renowned for the occurrence of different ecotypes linked to resource and habitat use throughout North America. We aimed to unravel the fine genetic structure of the four lake trout ecotypes in Lake Superior. A total of 486 individuals from four sites were genotyped at 6822 filtered SNP s using RAD seq technology. Our results revealed different extent of morphological and genetic differentiation within the different sites. Overall, genetic differentiation was weak but significant and was on average three times higher between sites (mean F ST = 0.016) than between ecotypes within sites (mean F ST = 0.005) indicating higher level of gene flow or a more recent shared ancestor between ecotypes within each site than between populations of the same ecotype. Evidence of divergent selection was also found between ecotypes and/or in association with morphological variation. Outlier loci found in genes related to lipid metabolism and visual acuity were of particular interest in this context of ecotypic divergence. However, we did not find clear indication of parallelism at the genomic level, despite the presence of phenotypic parallelism among some ecotypes from different sampling sites. Overall, the occurrence of different levels of both genomic and phenotypic differentiation between ecotypes within each site with several differentiated loci linked to relevant biological functions supports the presence of a continuum of divergence in lake trout.

Atlas-Based Automatic Generation of Subject-Specific Finite Element Tongue Meshes - Ahmad Bijar; Pierre-Yves Rohan; Pascal Perrier; Yohan Payan (Annals of Biomedical Engineering, 2016)

Optimal speech motor control and token-to-token variability: a Bayesian modeling approach - Jean-François Patri; Julien Diard; Pascal Perrier (Biological Cybernetics, 2015)

Stable isotope analyses on archived fish scales reveal the long‐term effect of nitrogen loads on carbon cycling in rivers - Jean‐Marc Roussel; Charles Perrier; Jaakko Erkinaro; Eero Niemelä; Richard A. Cunjak; Dominique Huteau; Pascal Riera (Global Change Biology, 2014)
Stable isotope analysis of organic matter in sediment records has long been used to track historical changes in productivity and carbon cycling in marine and lacustrine ecosystems. While flow dynamics preclude stratigraphic measurements of riverine sediments, such retrospective analysis is important for understanding biogeochemical cycling in running waters. Unique collections of riverine fish scales were used to analyse δ 15 N and δ 13 C variations in the food web of two European rivers that experience different degrees of anthropogenic pressure. Over the past four decades, dissolved inorganic N loading remained low and constant in the Teno River (70°N, Finland); in contrast, N loading increased fourfold in the Scorff River (47°N, France) over the same period. Archived scales of Atlantic salmon parr, a riverine life‐stage that feeds on aquatic invertebrates, revealed high δ 15 N values in the Scorff River reflecting anthropogenic N inputs to that riverine environment. A strong correlation between dissolved inorganic N loads and δ 13 C values in fish scales was observed in the Scorff River, whereas no trend was found in the Teno River. This result suggests that anthropogenic N‐nutrients enhanced atmospheric C uptake by primary producers and its transfer to fish. Our results illustrate for the first time that, as for lakes and marine ecosystems, historical changes in anthropogenic N loading can affect C cycling in riverine food webs, and confirm the long‐term interactions between N and C biogeochemical cycles in running waters.